The biomaterial polyphosphate blocks stoichiometric binding of the SARS-CoV-2 S-protein to the cellular ACE2 receptor. (14th October 2020) - Müller, Werner E. G.; Neufurth, Meik; Schepler, Hadrian; Wang, Shunfeng; Tolba, Emad; Schröder, Heinz C.; Wang, Xiaohong
Abstract : The polymer polyphosphate, abundant in blood platelets, blocks the binding of the receptor-binding domain (RBD) of the SARS- spike (S)-protein to the angiotensin-converting enzyme 2 (ACE2) at low concentrations. Abstract : The effect of the polyanionic polymer of inorganic polyphosphate (polyP) involved in innate immunity on the binding of the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein to the cellular ACE2 receptor was studied. The RBD surface comprises a basic amino acid stretch of four arginine residues which interact with the physiological polyP (polyP40 ) and polyP3 . Subsequently, the interaction of RBD with ACE2 is sensitively inhibited. After the chemical modification of arginine, an increased inhibition by polyP, at a 1 : 1 molar ratio (polyP : RBP), is measured already at 0.1 μg mL −1 . Heparin was ineffective. The results suggest a potential therapeutic benefit of polyP against SARS-CoV-2 infection.